Ubiquitination of IgG1 cytoplasmic tail modulates B-cell signalling and activation. (1st February 2020) - Kodama, Tadahiro; Hasegawa, Mika; Sakamoto, Yui; Haniuda, Kei; Kitamura, Daisuke
Abstract: Upon antigen stimulation, IgG + B cells rapidly proliferate and differentiate into plasma cells, which has been attributed to the characteristics of membrane-bound IgG (mIgG), but the underlying molecular mechanisms remain elusive. We have found that a part of mouse mIgG1 is ubiquitinated through the two responsible lysine residues (K378 and K386) in its cytoplasmic tail and this ubiquitination is augmented upon antigen stimulation. The ubiquitination of mIgG1 involves its immunoglobulin tail tyrosine (ITT) motif, Syk/Src-family kinases and Cbl proteins. Analysis of a ubiquitination-defective mutant of mIgG1 revealed that ubiquitination of mIgG1 facilitates its ligand-induced endocytosis and intracellular trafficking from early endosome to late endosome, and also prohibits the recycling pathway, thus attenuating the surface expression level of mIgG1. Accordingly, ligation-induced activation of B-cell receptor (BCR) signalling molecules is attenuated by the mIgG1 ubiquitination, except MAP kinase p38 whose activation is up-regulated due to the ubiquitination-mediated prohibition of mIgG1 recycling. Adaptive transfer experiments demonstrated that ubiquitination of mIgG1 facilitates expansion of germinal centre B cells. These results indicate that mIgG1-mediated signalling and cell activation is regulated by ubiquitination of mIgG1, and such regulation may play a role in expansion of germinal centre B cells. Abstract : Ubiquitination of IgG1 modulates BCR signaling